Pengaruh Karakteristik Individu dan Disiplin Kerja terhadap Kinerja Pegawai Sekretariat Daerah Kabupaten Aceh Barat - Fardila, Sri Tika; Jalil, Ivon (Medan Resource Center, 2023)
This article aims to determine the effect of individual characteristics and work discipline on the performance of West Aceh Secretariat employees. Each employee certainly has different individual characteristics for each employee and requires optimal work discipline, in order to achieve better employee performance. This research is a quantitative research. The sampling technique used was simple or random sampling by determining the number of other samples using the Oto Slovin formula and a total sample of 62 infected employees. Source of data obtained from primary data by distributing questionnaires. The analysis used in this study is multiple linear regression analysis (multiple regression). The results of this study indicate that 1) there is an effect of individual characteristics on employee performance, 2) there is an effect of work discipline on employee performance, 3) simultaneously individual characteristics of work discipline standards influence employee performance in West Aceh Region. Secretariat. employees with Fcount (94.189) greater than Ftable (3.156) with a significant value of 0.000.